Insights Into Long Non-Coding RNA and mRNA Expression in the Jejunum of Lambs Challenged With Escherichia coli F17 - Chen, Weihao; Lv, Xiaoyang; Zhang, Weibo; Hu, Tingyan; Cao, Xiukai; Ren, Ziming; Getachew, Tesfaye; Mwacharo, Joram M.; Haile, Aynalem; Sun, Wei (Frontiers in Veterinary Science, 2022)
It has long been recognized that enterotoxigenic Escherichia coli (ETEC) is the major pathogen responsible for vomiting and diarrhea. E. coli F17, a main subtype of ETEC, is characterized by high morbidity and mortality in young livestocks. However, the transcriptomic basis underlying E. coli F17 infection has not been fully understood. In the present study, RNA sequencing was conducted to explore the expression profiles of mRNAs and long non-coding RNAs (lncRNAs) in the jejunum of lambs who were identified as resistance or sensitive to E. coli F17 obtained in a challenge experiment. A total of 772 differentially expressed (DE) mRNAs and 190 DE lncRNAs were detected between the E. coli F17- resistance and E. coli F17-sensitive lambs (i.e. TFF2, LOC105606142, OLFM4, LYPD8, REG4, APOA4, TCONS_00223467 and TCONS_00241897). Then, a two-step machine learning approach (RX) combination Random Forest (RF) and Extreme Gradient Boosting (XGBoost) were performed and identified 16 mRNAs and 17 lncRNAs as potential biomarkers, within which PPP2R3A and TCONS_00182693 were prioritized as key biomarkers involved in E. coli F17 infection. Furthermore, a functional enrichment analysis showed that PPAR pathway was significantly enriched in response to E. coli F17 infection. Our findings provide insights into transcriptomic changes that occur in the host in response to E. coli F17 infection.